Halophilic microorganisms from Romanian saline environments as a source of extracellular enzymes with potential in agricultural economy - Mădălin Enache; Simona Neagu; Roxana Cojoc (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Halophilic microorganisms, either bacteria or archaea, flourish in media with salinity levels varying from negligible until to saturation in NaCl and thus are considered extremophiles. Such kinds of media as salt lakes, salted soils, salt deposits or salt mines are widely distributed over the entire Romanian landscape. Several strains of halophilic bacteria and archaea have been isolated from such environments and characterized either by polyphasic taxonomy approach or by their ability to produce extracellular enzymes with putative potential for use in several domains like industry, agriculture and biotechnology. Even if sodium chloride is widely used in Romanian agriculture fields, little is known about salt microbiota, and its effect on the agricultural processes. This paper approaches the wide spectrum of extracellular hydrolytic enzymes with putative use in agriculture for treatment of polluted soils or recovery of salted soils. The strains isolated from inside of salt crystal are divided in two groups, one consisting of six strains belonging to Halorubrum, Haloarcula and Halobacterium genera and characterized by the absence of detectable extracellular enzymatic activity for the tested substrates and the other group consisting of four strains, all belonging to Halorubrum genus and characterized by the presence of amylolytic activity and the absence of other activities. The starch degrading enzymes appear to have a wide distribution both among the strains associated with salt lakes and among those isolated from rock salt.
Keywords: 330; halophilic enzyme; halophilic microorganisms; salted soil; salt